ANALISIS LEARNING AND INOVATION SKILLS MAHASISWA PAI MELALUI PENDEKATAN SAINTIFIK DALAM IMPLEMENTASI KETERAMPILAN ABAD 21 - Bobi Erno Rusadi; Rohmat Widiyanto; Rahmat Rifai Lubis (Conciencia, 2019)
The research aims to describe the skill of Islamic education student in developing learning and innovation skills of student through a scientific approach. This study used a qualitative method based on descriptive analytic. The subjects of this research were 20 Islamic education students of Syarif Hidayatullah State Islamic University and North Sumatera State Islamic University who were carrying out practice of teaching in school. The subjects were chosen based on the the purpose of this study, thus the subjects were only students who used a scientific approach. Data collection is done by using interviews, observation, and study documentation. The study was conducted in July to October 2019. The results of this study showed that the ability of Islamic education students to observing aspects 80.63%, questioning aspects 75%, information gathering aspects (experimenting) 65%, reasoning/ associating aspects 78%, and communicating (comunicating) aspects 51.67% . Furthermore, in the average, the overall learning activity was carried out by islamic education teacher prospective students in developing learning and innovation skills with a scientific approach of 70.06% was achieved in a good category.